Regional studies : the interplay of land and people - Lich, Glen E., 1948- (Essays on the American West, 1992)
What makes a region a region, and how does one region differ from another? What are the tests of evidence of regionalism? What boundaries have meaning--political, geophysical, economic, cultural, psychological, ethnic, linguistic? Are there special problems in reporting findings about life within a region? These questions and others regarding methods and interdisciplinary content run through this stimulating series of papers on the interplay of land and people. While the.